(3YfGUQ GdGfJGL aj GdEbJUGO GdESdGej hGdEbJUGO GdhVYjs (3OQGSI ebGQfIs - (3GdHOhj(B, (3ESeGYjd EHQGgjes ((3GdchjJs (3eLdS GdfTQ GdYdejs, 2002)
(3eGgjI Yde GdGbJUGO jMJhj Ydi JYQjaGJ Yde GdGbJUGO,fTCI Yde GdGbJUGO,hehVhYg hCgOGag,hJejjRg Yf GdfXGe GdGbJUGOj hGdSjGSI GdGbJUGOjI,GdGfJGL hYfGUQg hjMJhj CgOGa GdGfJGL,YfGUQ GdGfJGL,GdCQV aj GdGbJUGO GdGSdGej hGdGbJUGO GdhVYj,GdCQV aj GdGbJUGO GdhVYj,GdehGQO GdGbJUGOjI aj GdGbJUGO GdGSdGej,GdYed aj GdGbJUGO GdGSdGej hGdfXe GdeYGUQI,GdYed aj GdfXe GdeYGUQI,GdYed aj GdTQjYI GdGSdGejI,QCS GdeGd aj GdGbJUGO GdESdGej hGdEbJUGO GdhVYj,GdJfXje hGdEOGQI aj GdGbJUGO GdGSdGej hGdGbJUGO GdhVYjs
Keywords: (3GdGbJUGO GdGSdGejs